REVISITING THE PAST FROM LITERATURE TO FILM: O SOBRADO AS A FILM ADAPTATION - Pereira, Mateus da Rosa (Laboratório Editorial FCL-UNESP, 2012)
This paper analyzes, from a comparative perspective, “O Sobrado,” a chapter from the novel O Continente (1949), by Erico Verissimo, and its film adaptation, O Sobrado (1956), directed by Walter George Durst and Cassiano Gabus Mendes. Based on an interdisciplinary approach, drawing on tools from the domains of literature and cinema, one of the goals of this paper is to propose film adaptation analyses which go beyond the debate on the fidelity of the film based on terms exclusively focused on the plot of the literary work, thus exploring other elements, such as mise-en-scene, photography, editing and sound. By addressing the context of production of the film, as a late product of Cia. Cinematográfica Vera Cruz, one of the main arguments of this study is that the novel and film protagonist, Licurgo Cambará, undergoes a process of “emptying” which implies deep changes in elements related to the narrative and visual style of the film in relation to the literary work. However, instead of adaptation flaws, the paper argues that such changes are in tune with the total organization of the film and with its artistic and production context, thus generating a different relationship with the representation of the past, which is consciously constructed in the film.